Species delimitation analyses of NE Atlantic Chaetozone (Annelida, Cirratulidae) reveals hidden diversity among a common and abundant marine annelid - Grosse, Maël; Bakken, Torkild; Nygren, Arne; Kongsrud, Jon A.; Capa, María (Molecular Phylogenetics and Evolution, 2020)
The polychaetes of the family Cirratulidae (Annelida) are common inhabitants in continental shelf benthic environments and considered an important group of organisms in environmental monitoring surveys. The family represents a taxonomic and systematic challenge, as monophyly of genera and evolutionary relationships within the family remain to be explored in a proper phylogenetic framework. Bitentaculate cirratulids, especially the genus Chaetozone, form one of the most species-diverse group of polychaetes worldwide. In this study, we aimed at evaluating the species diversity of the genus Chaetozonein benthic environments in the North East Atlantic by molecular means. We tested whether traditional morphological diagnostic characters are able to discriminate between the species hypothesis after species delimitation analyses, and assessed monophyly of the genera involved. Two DNA markers were sequenced from about 200 specimens belonging to Chaetozone, Aphelochaeta, Dodecaceria, Cirriformia and Cirratulus – the universal mitochondrial barcoding region COI, and the D1-D2 regions of the nuclear 28S rRNA – and analyzed with Bayesian inference, Maximum Likelihood and the species delimitation methods mPTP and GMYC. The first phylogeny of the family Cirratulidae is inferred and the genera Chaetozone, Dodecaceria and Cirratulus are recovered monophyletic. A total of 14 clusters of sequences – corresponding to species of Chaetozone – were found in the study area, and only one of them is here referred to a nominal species, Chaetozone setosa. Our results reveal several species complexes in the genus Chaetozone, that some of these independent lineages are unnamed and undescribed, and that morphological diagnostic features are in most cases unable to discriminate between the most similar species.
World Polychaeta Database (WPolyDb)